Analysis of the Free Nutritious Meal (MBG) Program Menu Using the Importance–Performance Analysis (IPA) Method - Ferdiansyah Ferdiansyah; Darmin Darmin; Nur Husnul Khatimah; Muammar Iksan (Universitas Muhammadiyah Palembang, 2026)
The Free Nutritious Meal (MBG) Program is designed to support students’ nutritional needs through the provision of safe, nutritious, and acceptable school meals. The success of the program depends not only on nutritional adequacy and food safety but also on menu acceptability and the extent to which service performance meets beneficiaries’ expectations. This study aimed to analyze the importance and performance of MBG menu attributes and to identify priority areas for improvement using Importance–Performance Analysis (IPA). A descriptive quantitative cross-sectional study was conducted from May to June 2026 in Wera District, Bima Regency. A total of 175 students aged 17–18 years who had received and consumed MBG meals were recruited using purposive sampling. Data were collected using a five-point Likert-scale questionnaire assessing the importance and performance of ten menu attributes. The analysis included mean scores, gap analysis, conformity levels, and Cartesian IPA mapping. The mean importance score was 4.72, while the mean performance score was 4.20, resulting in an average gap of ?0.52 and an overall conformity level of 88.93%. The largest gaps were identified in fruit and vegetable availability (?0.70) and menu variety (?0.68). Nutritional completeness, fruit and vegetable availability, and food taste were classified as high-priority attributes for improvement. Food hygiene, ingredient freshness, and food safety were categorized as attributes whose performance should be maintained. Overall, the MBG menu was rated positively, although its performance had not fully met students’ expectations. Improvement efforts should prioritize nutritional completeness, fruit and vegetable provision, and food taste, while menu variety should be evaluated continuously. This study assessed students’ perceptions and did not measure changes in nutritional status or academic performance.